Functional analysis of TM6 MADS-Box gene in the octoploid strawberry by CRISPR/Cas9 directed mutagenesis - Martín-Pizarro, Carmen; Posé-Padilla, David (My University, 2019)
The B-class of MADS-box transcription factors has been studied in many plant species, but remain functionally uncharacterized in Rosaceae. APETALA3 (AP3), a member of this class, controls petal and stamen identities in Arabidopsis. In this study, we identified two members of the AP3 lineage in the cultivated strawberry (Fragaria x ananassa): FaAP3 and FaTM6. Interestingly, FaTM6, and not FaAP3, shows an expression pattern equivalent to that of AP3 in Arabidopsis. Genome editing using CRISPR/Cas9 system is becoming a robust tool for targeted and stable DNA mutagenesis. However, whether it can be efficiently used in an octoploid species such as F. x ananassa is not yet established. Here we report the application of CRISPR/Cas9 to characterize the function of FaTM6 in strawberry flower development. An analysis by high-throughput sequencing of the FaTM6 locus spanning the target sites showed a highly efficient genome editing already in the T0 generation. The phenotypic characterization of the mutant lines indicates that FaTM6 plays a key role in anther development in strawberry. Our results validate the CRISPR/Cas9 strategy for gene functional analysis in F. x ananassa as an octoploid species, and they offer new opportunities for engineering strawberry to improve traits of interest in breeding programs.
Keywords: Fresas; Strawberry; Genome Editing; CRISPR/Cas9; Flower; Stamen; TM6; AP3; Homeotic gene